An Unexpected Cause of Sudden Death Reported as a Case of Adverse Event Following Immunization (AEFI) - Sam , N M; Raveendran , R; Deepthi , S (Journal of Indian Academy of Forensic Medicine, 2023)
Adverse event following immunization is any untoward medical occurrence which follows immunization and which does not necessarily  have a causal relationship with the usage of the vaccine. Here we had a case where a 20-year-old male, who had taken second dose of  Covishield vaccine and presented with complaints of fever, vomiting and abdominal pain. He was managed conservatively, but he  collapsed and died at home, the next day. Autopsy revealed it as a case of small bowel volvulus with complications like gangrene and  peritonitis. Volvulus of small intestine is a rare condition; non-specific clinical features and laboratory investigations make it difficult to  diagnose. Coincidence with vaccination perhaps complicated the diagnosis in this case, which needed to be dealt as a surgical emergency.
Keywords: Adverse event; Immunization; Covishield; Small bowel volvulus